The vital role of exercise and nutrition in COVID-19 rehabilitation: synergizing strength - Brent M. Peterson; Isabelle Unger; Sunny Sun; Ji-Yeun Park; Jinsil Kim; Richard S. Gunasekera; Jason Wilson; Thushara Galbadage (Frontiers Media S.A., 2023)
Since the outset of the COVID-19 pandemic, the global healthcare community has faced the challenge of understanding and addressing the ongoing and multi-faceted SARS-CoV-2 infection outcomes. As millions of individuals worldwide continue to navigate the complexities of post-hospitalization recovery, reinfection rates, and the increasing prevalence of Long-COVID symptoms, comprehensive COVID-19 rehabilitation strategies are greatly needed. Previous studies have highlighted the potential synergy between exercise and nutrition, suggesting that their integration into patient rehabilitation programs may yield improved clinical outcomes for survivors of COVID-19. Our group aimed to consolidate existing knowledge following the implementation of patient, intervention, comparison, and outcome (PICO) search strategies on the distinct and combined impacts of exercise and nutrition interventions in facilitating the recovery of COVID-19 patients following hospitalization, with a specific focus on their implications for both public health and clinical practice. The incorporation of targeted nutritional strategies alongside exercise-based programs may expedite patient recovery, ultimately promoting independence in performing activities of daily living (ADLs). Nonetheless, an imperative for expanded scientific inquiry remains, particularly in the realm of combined interventions. This mini-review underscores the compelling prospects offered by an amalgamated approach, advocating for the seamless integration of exercise and nutrition as integral components of post-hospitalization COVID-19 rehabilitation. The pursuit of a comprehensive understanding of the synergistic effects and effectiveness of exercise and nutrition stands as a crucial objective in advancing patient care and refining recovery strategies in the wake of this enduring global health crisis.